The evolving spectrum of PRRT2-associated paroxysmal diseases - Ebrahimi-Fakhari, Darius; Saffari, Afshin; Westenberger, Ana; Klein, Christine (Brain, 2015)
Next-generation sequencing has identified mutations in the PRRT2 (proline-rich transmembrane protein 2) gene as the leading cause for a wide and yet evolving spectrum of paroxysmal diseases. PRRT2 mutations are found in the majority of patients with benign familial infantile epilepsy, infantile convulsions and choreoathetosis and paroxysmal kinesigenic dyskinesia, confirming a common disease spectrum that had previously been suggested based on gene linkage analyses and shared clinical features. Beyond these clinical entities, PRRT2 mutations have been described in other childhood-onset movement disorders, different forms of seizures, headache disorders, and intellectual disability. PRRT2 encodes a protein that is expressed in the central nervous system and is thought to be involved in the modulation of synaptic neurotransmitter release. The vast majority of mutations lead to a truncated protein or no protein at all and thus to a haploinsufficient state. The subsequent reduction of PRRT2 protein may lead to altered synaptic neurotransmitter release and dysregulated neuronal excitability in various regions of the brain, resulting in paroxysmal movement disorders and seizure phenotypes. In this review, we examine the genetics and neurobiology of PRRT2 and summarize the evolving clinical and molecular spectrum of PRRT2-associated diseases. Through a comprehensive review of 1444 published cases, we provide a detailed assessment of the demographics, disease characteristics and genetic findings of patients with PRRT2 mutations. Benign familial infantile epilepsy (41.7%; n = 602), paroxysmal kinesigenic dyskinesia (38.7%; n = 560) and infantile convulsions and choreoathetosis (14.3%; n = 206) constitute the vast majority of PRRT2-associated diseases, leaving 76 patients (5.3%) with a different primary diagnosis. A positive family history is present in 89.1% of patients; and PRRT2 mutations are familial in 87.1% of reported cases. Seventy-three different disease-associated PRRT2 mutations (35 truncating, 22 missense, three extension mutations, six putative splice site changes, and seven changes that lead to a complete PRRT2 deletion) have been described to date, with the c.649dupC frameshift mutation accounting for the majority of cases (78.5%). Expanding the genetic landscape, 15 patients with biallelic PRRT2 mutations and six patients with 16p11.2 microdeletions and a paroxysmal kinesigenic dyskinesia phenotype have been reported. Probing the phenotypic boundaries of PRRT2-associated disorders, several movement, seizure and headache disorders have been linked to PRRT2 mutations in a subset of patients. Of these, hemiplegic migraine emerges as a novel PRRT2-associated phenotype. With this comprehensive review of PRRT2-associated diseases, we hope to provide a scientific resource for informing future research, both in laboratory models and in clinical studies.
Gesehen am 06.07.2020